A MODEL OF PERSONNEL MANAGEMENT IN ACCORDANCE WITH THE PRINCIPLES OF SARANIYADHAMMA OF THE ADMINISTRATORS OF MAHACHULALONGKORNRAJAVIDYALAYA UNIVERSITY - Boonpoo, Manassanan; Thitavaddhano, Phramaha Yannawat; PhrakhruOpatnontakitti (Sakda Obhaso) (Journal of Educational Review Faculty of Education in MCU, 2024)
This research article aimed to propose a model of personnel management based on the principles of Srṇīyadhamma for administrators of Mahachulalongkornrajavidyalaya University. It was a mixed-method research with 3 research steps: Step 1: To study the needs of personnel management of administrators; this was a quantitative research using a questionnaire with a sample group of 269 university lecturers. The research instrument was a questionnaire. Data were analyzed using statistics: percentage, mean, standard deviation, and PNIModified. Step 2: Developing a model; this was a qualitative research by interviewing 7 key informants and organizing a focus group discussion with 9 experts. The research instruments were an interview form and focus group discussion questions. Data were analyzed using content analysis. Step 3: Evaluating the model; this was a quantitative research using an evaluation form with a sample group of 226 university lecturers. The research instrument was an evaluation form. Data were analyzed using statistics: percentage, mean, and standard deviation. The results of the research found that: Personnel administration model based on the principle of Srṇīyadhamma of the administrators of Mahachulalongkornrajavidyalaya University consisted of 4 components: Component 1: Principle of Mahachulalongkornrajavidyalaya University as a state-controlled university at the higher education level and also a university of the Thai Sangha. The personnel were important to the university in pushing and promoting the university to develop its units until success was achieved. Therefore, the principle Srṇīyadhamma should be applied in personnel administration development. Component 2: Objective to apply the Saraniyadhamma principle to personnel administration. Component 3: Administration; 1) Personnel administration of administrators, 2) The 6 Srṇīyadhamma principles: (1) Mettkyakamma, doing good to one another, (2) Mettkvacīkamma, speaking kindly to one another, (3) Mettmanokamma, wishing good to one another, (4) Sdhraṇabhogit, sharing things with one another, (5) Silsmaññatā, having good behavior together, (6) Diṭṭhismaññatā, having common opinions. 3) Integrated personnel administration based on the principle of Srṇīyadhamma of administrators. Component 4: Application and evaluation results of the model in overall, the evaluation results were at the highest level in all four dimensions: usefulness, accuracy, feasibility, and appropriateness, respectively. In summary, the research knowledge was SCIPP, which included S (Srṇīyadhamma), C (Creating environment), I (Inspection process), P (Personnel recruitment announcement), and P (Personnel training).